Molecular pathogenesis of Spondylocheirodysplastic Ehlers‐Danlos syndrome caused by mutant ZIP13 proteins. Issue 8 (9th July 2014) - Bin, Bum‐Ho; Hojyo, Shintaro; Hosaka, Toshiaki; Bhin, Jinhyuk; Kano, Hiroki; Miyai, Tomohiro; Ikeda, Mariko; Kimura‐Someya, Tomomi; Shirouzu, Mikako; Cho, Eun‐Gyung; Fukue, Kazuhisa; Kambe, Taiho; et al.
Abstract The zinc transporter protein ZIP13 plays critical roles in bone, tooth, and connective tissue development, and its dysfunction is responsible for the spondylocheirodysplastic form of Ehlers‐Danlos syndrome (SCD‐EDS, OMIM 612350). Here, we report the molecular pathogenic mechanism of SCD‐EDS caused by two different mutant ZIP13 proteins found in human patients: ZIP13G64D, in which Gly at amino acid position 64 is replaced by Asp, and ZIP13ΔFLA, which contains a deletion of Phe‐Leu‐Ala. We demonstrated that both the ZIP13G64D and ZIP13ΔFLA protein levels are decreased by degradation via the valosin‐containing protein (VCP)‐linked ubiquitin proteasome pathway. The inhibition of degradation pathways rescued the protein expression levels, resulting in improved intracellular Zn homeostasis. Our findings uncover the pathogenic mechanisms elicited by mutant ZIP13 proteins. Further elucidation of these degradation processes may lead to novel therapeutic targets for SCD‐EDS.